PELATIHAN TRANSAKSI DALAM PERUSAHAAN DAGANG PADA SISWA SMAN 2 JAKARTA - Adang, Ferry; Bryan Goodwin; Gilbertus Brian (Jurnal Serina Abdimas, 2025)
The digital era demands improved accounting literacy from an early age, including for high school students, so they can understand and apply basic accounting concepts in daily life as well as for future academic and professional purposes. SMAN 2 Jakarta, as a partner in this Community Service (PKM) activity, is committed to enhancing students' understanding of accounting but faces challenges in improving academic performance, particularly in understanding trading company transactions and the practical application of accounting. This PKM activity aims to increase students' knowledge and skills in recording transactions, preparing basic financial statements, and understanding the application of basic accounting in business activities. The methods used include theoretical explanations, interactive discussions, and case-based problem-solving exercises, conducted offline at the school. The results of the training show that this approach significantly improves students’ understanding of the trading company accounting cycle, including transaction recording, account classification, and preparation of income statements and basic balance sheets. Moreover, this activity also builds students’ confidence in participating in national-level accounting competitions. In conclusion, training using interactive and practical methods has proven effective in improving students’ accounting literacy and can serve as a training model for other schools. The outputs of this activity include scientific publication, presentation media, and the potential registration of copyright for the training module used. ABSTRAK Era digital menuntut peningkatan literasi akuntansi sejak dini, termasuk bagi siswa-siswi tingkat sekolah menengah atas, agar mampu memahami dan menerapkan konsep dasar akuntansi dalam kehidupan sehari-hari maupun untuk keperluan akademik dan profesional di masa depan. SMAN 2 Jakarta, sebagai mitra dalam kegiatan Pengabdian kepada Masyarakat (PKM), memiliki komitmen untuk meningkatkan pemahaman akuntansi siswa, namun menghadapi kendala dalam pencapaian prestasi akademik, terutama dalam memahami transaksi perusahaan dagang dan penerapan akuntansi praktis. Kegiatan PKM ini bertujuan untuk meningkatkan pengetahuan dan keterampilan siswa dalam mencatat transaksi, menyusun laporan keuangan sederhana, serta memahami penerapan akuntansi dasar dalam aktivitas bisnis. Metode yang digunakan meliputi pemaparan teori, diskusi interaktif, serta latihan soal berbasis studi kasus yang relevan, dan dilaksanakan secara luring di sekolah. Hasil pelatihan menunjukkan bahwa pendekatan ini mampu meningkatkan pemahaman siswa terhadap siklus akuntansi perusahaan dagang secara signifikan, termasuk dalam aspek pencatatan transaksi, klasifikasi akun, serta penyusunan laporan laba rugi dan neraca sederhana. Selain itu, kegiatan ini juga membangun kepercayaan diri siswa untuk mengikuti kompetisi akuntansi tingkat nasional. Kesimpulannya, pelatihan dengan metode interaktif dan aplikatif terbukti efektif dalam meningkatkan literasi akuntansi siswa dan dapat dijadikan sebagai model pelatihan serupa di sekolah lain. Luaran dari kegiatan ini berupa publikasi ilmiah, media presentasi, serta potensi pendaftaran hak cipta atas modul pelatihan yang digunakan.